Effect the administration of human chorionic gonadotrophin (hCG) hormone following superovulation treatment in buffalo - Polmer Situmorang (Indonesian Center for Animal Research and Development (ICARD), 2005)
A numbers of studies had been reported to evaluate the effect of hormone for superovulation treatment in buffaloes, however the numbers of embryo recovered is still very small. One of the limiting factors which affect the numbers of embryo recovered is preovulatery LH concentration. The experiment was carried out to study the effect of hCG following superovulation treatments in buffaloes as an effort to increase the embryo recovered. Ten (10) buffaloes in three different genotypes (Riverine, swamp and its crosses) were superovulated using follicle stimulating hormone (FSH). A total of 12 ml FSH (Folltropin) was injected intramuscularry twice a day with 12 hours interval in a decreasing doses for 4 days (2.5, 2.5; 2.0, 2.0; 1.0, 1.0 and 0.5, 0.5 ml). Prostaglandin was injected intramuscularry 2 days after the first injection of FSH followed by administration of 500 IU hCG two days later. At the same days of administration of hCG, artificial insemination (AI) using frozen semen was conducted and repeated again after 12 and 24 hours. Blood collecting was conducted 3 times a week for obtaining the progesteron level of plasma blood. Embryo was collected by non-surgically technique on day 6 of estrus cycle by flushing each horn of uterus with 500 ml Dubelco's Phosphat Buffer Saline (DBPS). Parameter recorded were diameter of ovary (DO), total corpus luteum (TCL), number of embryo collected (NE), percentage of recovery rate (%RR) and peak progesteron level (PP). Administration of hCG significantly increase the response of buffalo to superovulation treatment. The mean of DO (cm), TCL, NE and RR (%) was 4.0, 6.3, 2.1 and 37.2 and 4.5, 7.5, 3.9 and 48.1 for controll and 500 IU hCG respectively. The mean NE was significantly higher (P<0.05) in hCG than those control. The peak progesterone concentration was highly significant higher (P<0.01) in hCG (8.9 ng/ml) than those control (6.8 ng/ml). Both left and right ovary gave a similar response to superovulation treatments. In conclusion the admission of hCG following superovulation treatments using folltrophin increase the number of embryos recovered. Key Words: hCG, Superovulation, Buffalo, Embryo